2022
DOI: 10.3390/antibiotics11010090
|View full text |Cite
|
Sign up to set email alerts
|

Multi-Drug and β-Lactam Resistance in Escherichia coli and Food-Borne Pathogens from Animals and Food in Portugal, 2014–2019

Abstract: Animal and food sources are seen as a potential transmission pathway of antimicrobial resistance (AMR) to humans. The aim of this study is to describe Campylobacter, Salmonella, and commensal Escherichia coli multi-drug resistance (MDR) in the food chain between 2014 and 2019 in Portugal. AMR surveillance data from food-producing animals and food were assessed. MDR relative frequencies were estimated by bacterial genus and year. AMR profiles were created using observations of resistance to antimicrobial classe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 45 publications
(55 reference statements)
1
2
0
Order By: Relevance
“…Overall, 64% of the tested isolates (57% from healthcare settings and 43% from swine) were resistant to three or more classes of antimicrobials and were thereby classified as MDR. MDR E. coli have been widely reported in livestock [15,38,39], food [40] and nosocomial infections [41][42][43][44][45]. As expected, the highest resistance rates to most of the substances, including AMP, SME, TRI, CIP, NAL and AZI, were found in isolates from hospital patients.…”
Section: Discussionsupporting
confidence: 62%
“…Overall, 64% of the tested isolates (57% from healthcare settings and 43% from swine) were resistant to three or more classes of antimicrobials and were thereby classified as MDR. MDR E. coli have been widely reported in livestock [15,38,39], food [40] and nosocomial infections [41][42][43][44][45]. As expected, the highest resistance rates to most of the substances, including AMP, SME, TRI, CIP, NAL and AZI, were found in isolates from hospital patients.…”
Section: Discussionsupporting
confidence: 62%
“…Hence, studying the distribution of ESBL isolates in various environments can help health authorities to take control measures [17]. It has been indicated that multiple drug resistance had been more frequent in E. coli when compared to Salmonella and Campylobacter isolates [18]. It has been shown that the ESBL-producing E. coli is nowadays eight times more prevalent when compared to the last two decades with a prevalence of around 2.6% in 2003 that reached 21.1.% in 2018 [19].…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, antimicrobial-resistant (AMR) bacteria have been admitted as a public health risk that could cause an increase in the global burden of infectious disease [1][2][3][4]. For instance, each year, more than 670,000 infections and 700,000 deaths worldwide were provoked by AMR [5,6]. Mutually controlled by host immune condition, microflora organization, and antimicrobial interventions, AMR evolu-tion occurs with the multidrug resistance [7,8].…”
Section: Introductionmentioning
confidence: 99%